Integrating ecology into rodent pest management in oil palm agroecosystem - Puan, Chong Leong (Universiti Putra Malaysia Press, 2013)
In Malaysia, palm oil production is a lucrative industry that contributes to the generation of national income and jobs to the nation. The perennial palms produce fruit bunches continuously throughout the year and are planted at a large scale in the country. Similar to other crops, oil palm planting suffers from damage by pests, with rodents being most serious. Even though biological control has been practiced, most plantations still reply on the use of rodenticide to combat rodent pests. Undeniably, chemical control often provides an immediate result in the elimination or reduction of pest numbers, although it also leads to other environmental problems including secondary poisoning of non-target animals and physiological resistance of target animals. This book explored the interactions among the biotic communities (namely rodents and their predators), food resources and habitat structure in oil palm plantations which are often overlooked in the management of such agroecosystem. The relationships among these elements that have been empirically examined in the field suggested that an integrated and adaptive approach should be employed with the incorporation of ecological knowledge